Agensi Kelembagaan Modal Sosial Dalam Tata Kelola Wisata Bahari di Pantai Martajasah, Kabupaten Bangkalan, Jawa Timur - Purwanto, Edy; Mulyaningsih, Hetti (Indonesian Journal of Tourism and Leisure, 2024)
This article aim to explore the social capital strategy in marine tourism governance which crucially contributes as strength and resilience in maintaining the sustainability principles of tourist destinations that are experiencing the challenges of social change. This study uses the theory of practice social capital approach from Pierre Bourdieu with qualitative research methods and an analytical-case approach using observation techniques, in-depth interviews and focus group discussions which are concentrated on the aspect of tourism governance. The findings of this study succeeded in revealing that the cross-sectoral institutional agency network model in Martajasah beach produced a “capital reproductive strategy” and “capital conversion strategy”. First, the existence of the capital reproduction strategy has succeeded in urging the authorities of the "state apparatus" in spreading network to collaborate between the tourism office, the marine service and private companies. Second, the conversion strategy seeks to be intertwined with community leaders, NGOs and educational institutions as a trinity of "institutionalized cultural capital" which has the "rules of the game" in exchanging social capital into cultural capital to support the quality of tourism attraction governance through donations and training. Capital reproduction strategy and capital conversion strategy are the power of social capital where resources can be accumulated in turning vulnerability into resilience so that Martajasah beach can be maintaining the "status quo" as a leading tourist destination in the dynamics of social change.